Devsecops methodology for NG-IoT ecosystem development lifecycle - assist-IoT perspective - López, Óscar; Blasi, Jordi; Uriarte, Mikel; Lacalle, Ignacio; Galiana, Gonzalo; E. Palau, Carlos; Garro, Eduardo; Ganzha, Maria; Paprzycki, Marcin; Lewandowski, Piotr; Wasielewska, Katarzyna; Votis, Konstantinos; et al. (Journal of Computer Science and Cybernetics, 2021)
Current software projects require continuous integration during their whole lifetime. In this context, different approaches regarding introduction of DevOps and DevSecOps strategies have been proposed in the literature. While DevOps proposes an agile methodology for the development and instantiation of software platforms with minimal impact in any kind of operations environment, this contribution proposes the introduction of DevOps methodology for Next Generation IoT deployments. Moreover, novelty of the proposed approach lies in leveraging DevSecOps in different stages and layers of the architecture. In particular, the present work describes the different DevSecOps methodology tasks, and how the security is included on pre-design activities such as planning, creation or adaptation, the design and implementation, as well as on post-implementation activities such as detection, response. Without proper consideration of security and privacy best practices identified in this article, the continuous delivery of services using DevOps methodologies may create risks and introduce different vulnerabilities for Next Generation IoT deployments.